2004
DOI: 10.1073/pnas.0306764101
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamics of HIV-1 recombination in its natural target cells

Abstract: Genetic recombination is believed to assist HIV-1 diversification and escape from host immunity and antiviral therapies, yet this process remains largely unexamined within the natural target-cell populations. We developed a method for measuring HIV-1 recombination directly that employs reporter viruses bearing functional enhanced yellow fluorescent protein (YFP) and enhanced cyan fluorescent protein (CFP) genes in which recombination produces a modified GFP gene and GFP fluorescence in the infected cells. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

37
526
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 406 publications
(564 citation statements)
references
References 46 publications
(49 reference statements)
37
526
1
Order By: Relevance
“…2d does not vanish but eventually rises again following predator-prey dynamics (9), so T* also has a late rise.] This overall two-phase dynamics is similar to the infected cell dynamics observed in in vitro experiments (2). With the overall dynamics thus qualitatively mimicking experiments, we employ this description to investigate the dynamics of multiple infections.…”
Section: Model Calculationssupporting
confidence: 58%
See 2 more Smart Citations
“…2d does not vanish but eventually rises again following predator-prey dynamics (9), so T* also has a late rise.] This overall two-phase dynamics is similar to the infected cell dynamics observed in in vitro experiments (2). With the overall dynamics thus qualitatively mimicking experiments, we employ this description to investigate the dynamics of multiple infections.…”
Section: Model Calculationssupporting
confidence: 58%
“…3 as parametric plots of T* i (t) vs. T* 1 (t). Recall that Levy et al (2) found that coinfected cells, presumably mostly T* 2 , are proportional to (T* 1 ) 2 . (Note that T* 2 Ͻ Ͻ T* 1 in their experiments except near peak infection so that T* 1 Ϸ T*.)…”
Section: Model Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a recent study of the dynamics of HIV-1 recombination suggests that HIV-1 may have evolved high recombination rates to foster rapid diversification and further its survival (66).…”
Section: Implications For Evolutionmentioning
confidence: 99%
“…Indeed, ex vivo experiments in HeLa CD4 ϩ -infected cells estimated that three events of template switching occur, on average, per replication cycle (16). Furthermore, it has recently been shown that the recombination rates are influenced by the type of cell infected, with the highest rates observed in macrophages (17). A crucial issue to address now is whether this high rate results from the presence of recombination hot spots interspersed among sequences yielding low recombination rates, or if it reflects a nearly constant frequency of strand transfer along the whole genome.…”
mentioning
confidence: 99%